(untitled) (Journal of Applied Learning and Teaching, 2021)
The rising popularity of learning via e-learning platforms, coupled with the accelerated pace in mobile devices’ uptake during the post-COVID-19 environment, presents tremendous learning demands on mobile and wireless networking infrastructure. Some fundamental principles and components are essential to maximizing user experience and online program success. This paper will explore the gaps between traditional learning and mobile learning by presenting a comprehensive survey of the two areas’ cusps. We trace the practices in mainstream schools with potential online program development and delivery strategies to meet the school’s ratification. We identify the critical learning and performance support. We then discuss several techniques and platforms that facilitate the efficient deployment of learning onto mobile systems. Finally, we discuss how to tailor learning to mobile environments, propose a set of activities that would augment online presence for students, and open directions for future research.